MDMA Abuse in Relation to MicroRNA Variation in Human Brain Ventral Tegmental Area and Nucleus Accumbens - (:unkn) unknown (SHAHEED BEHESHTI UNIV, SCH PHARMACY, 2019)
3,4-methylenedioxymethamphetamine (MDMA) is one of the most widespread illegal drugs, that have been used particularly by young people in the 15-34 age group. MicroRNAs (miRNAs) are endogenously synthesized, non-coding, and small RNA s that post-transcriptionally regulate their target genes' expression by inhibiting protein translation or degradation. miRNAs are increasingly implicated in drug-related gene expressions and functions. Notably, there are no reports of miRNA variation in the human brain in MDMA abuse. We here present a miRNA profiling study - the first such study, to the best of our knowledge - into the post-mortem human brains of a sample of people with MDMA abuse, along with non-drug dependent controls. The miRNA profiling of nucleus accumbens (NAc) and ventral tegmental areas (VTA) was performed by microarray analysis. Subsequently, two candidate miRNA putative biomarkers were selected according to significant regional differential expression (miR-1202 and miR-7975), using quantitative reverse-transcription PCR (qRT-PCR). We showed that the expression level of miR-7975 was significantly lower in the VTA regions of the 30 MDMA users, as compared with the 30 control samples. Another significantly deregulated miR-1202 was down-regulated in the NAc regions of 30 MDMA samples in comparison to the control samples. Alteration of these miRNAs can potentially serve as novel biomarkers for MDMA abuse, and warrant further research in independent and larger samples of patients.
Keywords: MicroRNA; 3,4-methylenedioxymethamphetamine; Ventral Tegmental Area; Nucleus Accumbens; Microarray research; MESOLIMBIC DOPAMINE SYSTEM; COCAINE; EXPRESSION; NEUROPLASTICITY; IDENTIFICATION; CONNECTIVITY; TRANSPORTERS; DATABASE; MIR-1202; ECSTASY